Oral Management of Children with Intellectual Disabilities Accompanied by Hypothyroidism - Syahrir, Syakriani (Hasanuddin University, 2021)
Objective: This case report will be discussing the dental and oral care of a child with intellectual disability and hypothyroid disease. Intraoral examination showed the residual teeth 16, superficial caries in teeth 26, agenesis 12, delayed resorption 53, maxillary anterior teeth diastemas, crowding of the lower anterior teeth, deep bite, glossitis, and macroglossia tongue.Method: Various methods of behavioral approach were carried out at each visit. Treatment began from changing children's behavior, providing dental health education, filling cavities, scalling and applying fluoride topically.Result: In six visits, noticeable changes in plaque scores are getting better and children were more cooperative, caries dental has successfully restored, and topical fluoride applied.Conclussion : Oral health management of patients with intellectual disabilities is different from normal patient. Dentists must approach the patient according to the level of intellectual disability and know the complications of hypothyroid disease to avoid complications during dental treatment.